Numerical Study of the Microflow Characteristics in a V-ball Valve - Zhi-xin Gao; Yang Yue; Jia-ming Yang; Jun-ye Li; Hui Wu; Zhi-jiang Jin (Micromachines, 2021)
V-ball valves are widely applied in many process industries to regulate fluid flow, and they have advantages of good approximately equal percentage flow characteristics and easy maintenance. However, in some applications, the V-ball valve needs to have good performance under both large and extremely small flow coefficients. In this paper, the improvement of the original V-ball valve is made and the flow characteristics between the original and the improved V-ball valve are compared. Two types of small gaps are added to the original V-ball, namely the gap with an approximately rectangular port and the gap with an approximately triangular port. The effects of the structure and the dimension of the gap on flow characteristics are investigated. Results show that within the gap, the flow coefficient increases but the loss coefficient decreases as the valve opening increases, and the flow coefficient has an approximately linear relationship with the flow cross-area of the added gap. Results also show that under the same flow cross-area, the flow coefficient has a higher value if the distance between the gap and the ball center is greater or if the gap is an approximately rectangular port, while the loss coefficient has an opposite trend.